Effects of dynamic response to coronavirus disease outbreak in a regional emergency medical center: A retrospective study. Issue 28 (16th July 2021) - Oh, Ye Jin; Kim, Gyun Moo; Ko, Seung Hyun; Seo, Young Woo; Lee, Suk Hee; Jang, Tae Chang
Abstract : Abstract: Emergency departments (EDs) are on the frontline of the coronavirus disease (COVID-19) outbreak. To resolve the abrupt overloading of COVID-19–suspected patients in a community, each ED needs to respond in various ways. In our hospital, we increased the isolation beds through temporary remodeling and by performing in-hospital COVID-19 polymerase chain reaction testing rather than outsourcing them. The aim of this study was to verify the effects of our response to the newly developed viral outbreak. The medical records of patients who presented to an ED were analyzed retrospectively. We divided the study period into 3: pre-COVID-19, transition period of response (the period before fully implementing the response measures), and post-response (the period after complete response). We compared the parameters of the National Emergency Department Information System and information about isolation and COVID-19. The number of daily ED patients was 86.8 ± 15.4 in the pre-COVID-19, 36.3 ± 13.6 in the transition period, and 67.2 ± 10.0 in the post-response period ( P  < .001). The lengths of stay in the ED were significantly higher in transition period than in the other periods [pre-COVID-19 period, 219.0 (121.0–378.0) min; transition period, 301 (150.0–766.5) min; post-response period, 281.0 (114.0–575.0) min; P  < .001]. The ratios of use of an isolation room and fever (≥37.5°C) were highest in the post-response period [use of isolation room: pre-COVID-19 period, 0.6 (0.7%); transition period, 1.2 (3.3%); post-response period, 16.1 (24.0%); P  < .001; fever: pre-COVID-19 period, 14.8(17.3%); transition period, 6.8 (19.1%); post-response period, 14.5 (21.9%), P  < .001]. During an outbreak of a novel infectious disease, increasing the number of isolation rooms in the ED and applying a rapid confirmation test would enable the accommodation of more suspected patients, which could help reduce the risk posed to the community and thus prevent strain on the local emergency medical system.